Two-stage cluster sampling with unequal probability sampling in the first stage and ranked set sampling in the second stage - Michael C. Ugwu; Mbanefo S. Madukaife (Statistics in Transition new series (SiTns), 2022)
In this research work we introduce a new sampling design, namely a two-stage cluster sampling, where probability proportional to size with replacement is used in the first stage unit and ranked set sampling in the second in order to address the issue of marked variability in the sizes of population units concerned with first stage sampling. We obtained an unbiased estimator of the population mean and total, as well as the variance of the mean estimator. We calculated the relative efficiency of the new sampling design to the two-stage cluster sampling with simple random sampling in the first stage and ranked set sampling in the second stage. The results demonstrated that the new sampling design is more efficient than the competing design when a significant variation is observed in the first stage units.
Keywords: 519; cluster sampling; population mean estimator; probability proportional to size sampling; ranked set sampling; relative efficiency